Gendered Realities in the Teaching Profession: Opportunities and Challenges Faced by Women in Haldibari Rural Municipality, Jhapa - Acharya, Pujan Kumari (Adhyayan Journal, 2026)
The Paper is an anthropological narrative on the ideological imaginary of professional identity, opportunities, and the challenges faced by women teachers in Haldibari Rural Municipality, Jhapa, Nepal. Although not all women teachers have a weak professional identity, mixed-methods approaches such as interviews, focus group discussions, and observations reveal that many women teachers express high levels of professional identity, manifested through both affective and technical competence. In the focus groups, respondents also pointed out that communication skills, tolerance, empathy, creativity, and caring about children are societal notions of female characteristics, based on the belief that these qualities are immutable elements of femininity that represent key teacher professional competencies. While brushing aside an assertion about the theory of emotional labor dependence on women, they pointed out new demands on modern teachers for teamwork across contexts, flexibility, and mental toughness. Women teachers are also affected by the competence and capacities of women teachers. The failure of women teachers to perform well is due to factors such as leadership, training, classroom size, lack of resources, low salaries, and policy neglect. However, the study also shows how patriarchal ideology is internalized, at times even by other women (particularly in leadership roles). Emerging — work and family balance influenced by distance and family obligations.